(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In the article, based on the analysis of various scientific concepts and theories, the process of modernization is considered, the socio-philosophical essence and conceptual foundations of the phenomenon and the process of “modernization” are determined. The study of modern theoretical and methodological approaches to the modernization phenomenon makes it possible to show its spiritual, cultural, philosophical and socio-philosophical aspects, as well as the importance and complexity of the differentiation of the process of transformation of social relations in its historical development. In the scientific analysis of the phenomenon and the process of modernization, the notion of “modern”, which is the theoretical basis of research, is a complex of systemic cultural-spiritual, historical-political, socio-economic processes in the development of society and the state. It is also demonstrated that modernization is the basis of universal, self-organizing transformations. The authors point out that the stability and security of the state, the improvement of the quality of life of citizens in society and the orientation towards the sustainable functioning of cultural institutions form the basis of the modernization process. In this context, the authors give priority to the study of the world outlook and social factors in the development of society. The concept of “modernization” is considered too general and is presented in various alternative concepts. Therefore, philosophical definitions and explanations of these concepts in all their diversity are analyzed and compared. Key words: modernization, tradition, capitalism, culture, self-determination.